Leakage-resilient certificateless signcryption scheme - Yan-lin QIN; Xiao-ping WU; Wei HU (Tongxin xuebao)
In practical applications,the potential adversary may exploit partial information about the secret keys by side-channel attacks ,traditional certificateless signcryption schemes can’t resist these key-leakage attacks.A leakage-resilient certificateless signcryption scheme based on Elliptic Curve Cryptography and bilinear pairing was presented.In the random oracle,proved that the security of the scheme is based on the decisional Diffie-Hellman assumption.The scheme is also proved semantically secure against adaptive posterior chosen-ciphertext key-leakage attacks (KL-CCA2),and existentially unforgeable against chosen-message key-leakage attacks(KL-CMA).The proposed scheme was free from non-interactive zero knowledge proof system and needs no bilinear paring operation in signcryption phase.Compared with other schemes of the same kind,the proposed scheme can resist key-leakage attacks and maintains high efficiency.